Analisis Strategi Promosi Media Sosial Terhadap Keputusan Mahasiswa dalam Memilih Institusi Pendidikan Tinggi - Eka Hendrayani; Rudy Irwansyah; Hadiansyah Ma'sum; Olivia Tahalele; Zunan Setiawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Social media promotion strategies have become an important foundation for young people in making college decisions. Education is the main pillar in community development. However, with increasing competition between universities, both state and private, new challenges have emerged. Universities must continue to improve their quality in order to remain relevant and competitive in the increasingly tight education market. This study aims to determine the effect of social media promotion strategy analysis on students' decisions in choosing higher education institutions. The research method used in this study is a quantitative descriptive method. The study was conducted at 5 universities in Indonesia with a student population of 100 respondents. The results of this study found that social media promotion strategies on students' decisions in choosing higher education institutions.